On Left Slides (Upper or Lower) in e-Abacus Diagram - Jwan Khairi Khaleel khalil; Ammar Mahmood (College of Education for Pure Sciences, 2023)
In recent years, there has been an increase in interest in researching various (movements) on the e-abacus diagram in attempt to determine how these movements affect the origin of the design as a form of coding. In this paper we will submit an technique is used for the first time, but from one diagram we will get several diagrams, so that they do not resemble each other except in specific parts of the diagram, which makes finding the original seem almost impossible. It will start from the bottom left side exclusively for the diagram and then in a manner similar to slides from the top to the bottom, and from the bottom to the top, followed by the top left side exclusively for the diagram and in the direction up to the bottom and finally down to the top. By dividing the diagram into slides just from the left side of the diagram, we will provide four new types in this research and in the upper or lower directions LSUUL, LSULU, LSLUL and LSLLU.